Investigating the Techniques Used by Iraqi Teachers in Teaching Reading Comprehension in the University Level - Shamma Mustafa Hameed, (International Journal of Psychosocial Rehabilitation, 2025)
In teaching English, Reading is an important and effective skill in the learning and teaching process. Therefore, teachers should focus on and teach strategies to help learners cope with the text. Subsequently, it is important to investigate teacher techniques in the classroom as they teach reading. This study was designed to investigate the teaching techniques of reading comprehension among Iraqi EFL teachers in Iraqi universities. The study used a fully quantitative research design to collect data through a survey questionnaire from 34 lecturers. The findings showed that teachers used various strategies which are divided into three categorizations namely; pre reading, while-reading, and post-reading. Strategies of previewing and vocabulary technique, Question-Answering Technique, vocabulary instruction technique, recitation and reading aloud reviewing technique and follow up strategy. An implication was drawn at the end of the study